Investigating Disturbances of Oxygen Homeostasis: From Cellular Mechanisms to the Clinical Practice - Tretter, Verena; Zach, Marie-Louise; Böhme, Stefan; Ullrich, Roman; Markstaller, Klaus; Klein, Klaus Ulrich (Frontiers in Physiology, 2020)
Soon after its discovery in the 18th century, oxygen was applied as a therapeutic agent to treat severly ill patients. Lack of oxygen, commonly termed as hypoxia, is frequently encountered in different disease states and is detrimental to human life. However, at the end of the 19th century, Paul Bert and James Lorrain Smith identified what is known as oxygen toxicity. The molecular basis of this phenomenon is oxygen’s readiness to accept electrons and to form different variants of aggressive radicals that interfere with normal cell functions. The human body has evolved to maintain oxygen homeostasis by different molecular systems that are either activated in the case of oxygen under-supply, or to scavenge and to transform oxygen radicals when excess amounts are encountered. Research has provided insights into cellular mechanisms of oxygen homeostasis and is still called upon in order to better understand related diseases. Oxygen therapy is one of the prime clinical interventions, as it is life saving, readily available, easy to apply and economically affordable. However, the current state of research also implicates a reconsidering of the liberal application of oxygen causing hyperoxia. Increasing evidence from preclinical and clinical studies suggest detrimental outcomes as a consequence of liberal oxygen therapy. In this review, we summarize concepts of cellular mechanisms regarding different forms of disturbed cellular oxygen homeostasis that may help to better define safe clinical application of oxygen therapy.